The Influence of Food Product Quality andService Quality on Purchase Decisions at 8Bars Resto & Bar Bekasi City - Sriwulandari, Tatik; Ramadhan, Rizky Alik (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
Product quality and service quality in the restaurant business are two important things that make customers make decisions to make purchases and come again to the restaurant. The purpose of this study was to determine the effect of food product quality and service quality on purchasing decisions at 8Bars Resto & Bar - Bekasi City. This research is quantitative research with an inductive, objective, and scientific approach where the data obtained is in the form of numbers. Data acquisition was assessed and analyzed statistically through the SPSS application with data collection techniques by distributing questionnaires to 100 respondents.The research results obtained showed that the quality of food products had a positive and significant effect on purchasing decisions with a t-count > t-table = 3.605 > 1.661 and a significance value of less than 0.05. Then the results of the value of Service Quality have a positive and significant effect on Purchase Decision with t-count > t-table = 5.711 > 1.661, then H0 is rejected on H1 is accepted. The test results between the two independent variables were simultaneously carried out with the F test and the results showed that the F-count was 63,948 while the F-table value was 3.090186675, meaning that Fcount > Ftable with a significance value of 0.000 <0.050. Based on these tests, it can be concluded that H0 is rejected and H1 is accepted. This means that the variables Product Quality (X1) and Service Quality (X2) have a positive and significant effect on Purchase Decision (Y) at 8Bar Resto and Bar Bekasi City and are proof that the needs and desires of its customers have been fulfilled. Furthermore, efforts need to be made to maintain product quality and service quality to anticipate competitors with the same type of business.